2006
DOI: 10.1111/j.1365-3156.2006.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal rubella serosurvey in Maputo, Mozambique

Abstract: Summaryobjective To describe the epidemiology of rubella in Mozambique. methods Cross-sectional serosurvey of rubella IgG antibodies among women attending antenatal clinics in Maputo in February-April 2002 to assess the prevalence and titres.results Rubella IgG antibodies were detected in 95.3% (95% confidence interval 94.0%-96.6%) of 974 pregnant women. Age and residence did not significantly affect the prevalence of rubella IgG antibodies. However, the mean titre of rubella IgG antibodies was higher in women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
27
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 10 publications
8
27
1
Order By: Relevance
“…Moreover, similar high rubella seroprevalence has been previously reported in many developing countries that were not using rubella vaccine [8], including countries from the World Health Organization Eastern Mediterranean Region, such as the Islamic Republic of Iran, where the seroprevalence of rubella was 91.1% among pregnant women [9]. In addition, a similar high rubella prevalence of 95.3% has been reported in some African countries, such as South Africa and Mozambique [10,11], besides, a slightly higher prevalence of 97.9% among Nigerian pregnant women [12].…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, similar high rubella seroprevalence has been previously reported in many developing countries that were not using rubella vaccine [8], including countries from the World Health Organization Eastern Mediterranean Region, such as the Islamic Republic of Iran, where the seroprevalence of rubella was 91.1% among pregnant women [9]. In addition, a similar high rubella prevalence of 95.3% has been reported in some African countries, such as South Africa and Mozambique [10,11], besides, a slightly higher prevalence of 97.9% among Nigerian pregnant women [12].…”
Section: Discussionsupporting
confidence: 71%
“…Our 351 finding of no statistically significant increases in rubella antibody seroprevalence with increasing age (after 352 approximately 15 years of age) has been observed in a number of the above-mentioned serosurveys and others 353 [34, 35, 39, 42-46, 48, 49, 53, 54]. Moreover, in agreement with published observations from other African 354 countries, for the assessment population in DRC overall, rubella antibody seroprevalence was similar among 355 19 women declaring residence in urban versus rural settings; however, differences in antibody seroprevalence were 356 observed between different geographic areas in the country [31,34,38,41,43,44,46,51]. Last and consistent 357 with reports from other African countries, age at first pregnancy, number of pregnancies, civil status, 358 educational level, and occupation were not associated with rubella antibody seroprevalence in DRC [34, 38, 41, 359 44-46, 53].…”
supporting
confidence: 78%
“…In Nigeria, it is found that 68.5% of pregnant women had Rubella infections (Bamgboye et al, 2004), whereas in incidence was reported in Mozambique, which was estimated as 95.3%. (Barreto et al, 2006). In mounting body of study conducted among Sudanese women, Rubella virus was detected in 65.3% (Hamdan et al, 2011) and 95.1% (Adam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some defects have been stated later following maternal infections in the second trimester (Ojala et al, 1973). Incidence of Rubella infection is becoming low globally, nevertheless, some African countries such as Mozambique estimated high incidence (95.3%) (Barreto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%